1986
DOI: 10.1093/nar/14.2.983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the polyamines spermine and spermidine on yeast tRNAphe as revealed from its imino proton NMR spectrum

Abstract: A comparison of imino proton NMR spectra of yeast tRNAPhe recorded at various solution conditions indicates, that polyamines have a limited effect on the structure of this tRNA molecule. Polyamines are found to catalyse the solvent exchange of several imino protons in yeast tRNAPhe not only of non hydrogen bonded imino protons, but also of imino protons of the GU and of some AU and tertiary base pairs. It is concluded that at low levels of catalysing components the exchange rates of the latter protons are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The increased exchange of O&N1 protons in the presence of spermidine has been noted previously (27,28) for the {55 NI proton in yeast tRNAPhe. 155 is in the T-loop of tRNA, where it is hydrogen-bonded through the C4 carbonyl to the G18 NI proton, and through the N3 proton to phosphate 58.…”
Section: Access To Spermidinesupporting
confidence: 68%
See 1 more Smart Citation
“…The increased exchange of O&N1 protons in the presence of spermidine has been noted previously (27,28) for the {55 NI proton in yeast tRNAPhe. 155 is in the T-loop of tRNA, where it is hydrogen-bonded through the C4 carbonyl to the G18 NI proton, and through the N3 proton to phosphate 58.…”
Section: Access To Spermidinesupporting
confidence: 68%
“…In the NMR experiments of Tropp and Redfield (27), the addition of spermidine to yeast tRNAPhe decreased the exchange rate of the 055 N3 proton, while that of the V55 NI proton was increased. This selective protection of 155 N3 H could be due to a specific interaction which stabilized the tertiary folding; the destabilization of NI H could be due to catalysis by the spermidine (28). Similarly, the non-hydrogen-bonded 639 NI proton disappears from the NMR spectrum when spermidine is present (28), while the hydrogen-bonded &39 N3 proton is stable.…”
Section: Access To Spermidinementioning
confidence: 99%
“…Considering the stringency of picornavirus packaging, if the recombinant RNA, in three-dimensional structure, is too voluminous to be encased in the rigid capsid, packaging pressure may cause a deletion of the nonessential foreign insert. The three-dimensional conformation of the insert RNA is associated, at least in part, with the number of hydrogen bonds in canonically base-paired regions and sequence-dependent free energy (4,6,15,31). Based on this rationale, we have studied the correlation between genetic stability and the G/C contents of each insert and found that most of the stable inserts showed a high G/C content of over 40% (Table 1 and Fig.…”
Section: Vol 76 2002 Design Architecture For Genetic Stability Of Rmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) has long been a powerful tool to monitor tRNA folding and conformation. The earliest studies of RNAs using NMR focused on the exchangeable imino proton spectrum of natural tRNAs that could be obtained in high yield [20,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The imino proton spectra of various tRNAs were assigned, and used to probe the folding and dynamics of tRNAs under different solution conditions.…”
Section: Introductionmentioning
confidence: 99%